EFFECT OF OXYTOCIN, PGF2α AND GnRH ON UTERINE INVOLUTION AND POSTPARTUM FERTILITY IN MURRAH BUFFALOES SUBJECTED TO FETOTOMY - WANI, A A; BHAT, M B; MAVI, P S; BRAR, P S (The Indian Journal of Animal Reproduction, 2022)
Out of dystocia affected Murrah buffaloes subjected to fetotomy operation (n=40), one group of 20 buffaloes was administered a) Oxytocin (50IU I/M) immediately and 4h after fetotomy, b) Prostaglandin F2α (500μg I/M on d7 and d21 postpartum), and c) GnRH (buserlin acetate @ 20μg I/M) on day 28 postpartum. The second group of 20 animals subjected to fetotomy were not administered any test medication. The third group consisting of 10 normally calving buffalo served as control. The buffaloes of frist group had improved uterine health, ovarian rebound and became pregnant in lesser time than others. In brief, administration of ecbolics and GnRH in early postpartum period hastens uterine involution and improves reproductive efficiency of dystocia affected buffaloes.